HUBUNGAN PENGETAHUAN DAN PERILAKU MASYARAKAT TENTANG SANITASI LINGKUNGAN DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI RW 10 KELURAHAN CIBEUNYING KABUPATEN BANDUNG - Tri Ardayani; Fahmi Fuadah; Dennis Setiadi (JURNAL KESEHATAN INDRA HUSADA, 2022)
Background. Dengue fever is one of the diseases that is a public health problem and is endemic. Bandung Regency is included in the top 5 regions with dengue cases in West Java Province. Poor environmental sanitation can cause various diseases, one of which is DHF disease. Purpose. To analyze the relationship of knowledge and behavior of the community regarding environmental sanitation to the incidence of dengue fever in RW 10 Cibeunying Village. Method. The research design used was descriptive quantitative with a population of 887 and a sample of 90 respondents. The calculation uses simple random sampling and data collection using accidental sampling techniques. Result. The correlation test using chi square on knowledge variables against the distance and DHF obtained the results of the sig value. 0.580>0.05 means that there is no significant relationship between knowledge and the incidence of DHF. The correlation test using chi square on behavioral variables against the dhf and DHF obtained the results of the sig value. 0.000<0.05 means that there is a significant relationship between knowledge and the incidence of DHF. Conclusion. There is no significant relationship between knowledge and dhf events, but there is a significant relationship between behavior and DHF events. Suggestion. Create a dengue prevention program that is not only an increase in knowledge but there is real action as well as from health workers or from the community. Keywords : Dengue Hemorrhagic Fever, Environmental Sanitation, Knowledge, Behavior.